KEABSAHAN PERJANJIAN KONTRAK ELEKTRONIK DALAM TRANSAKSI E-COMMERCE DI TINJAU DARI HUKUM PERDATA - Ikka Puspita Sari (AL WASATH Jurnal Ilmu Hukum, 2022)
ABSTRACT Transaction Media, which is more commonly referred to as E-Commerce, can be understood as a type of buying and selling transaction or trading of goods or services through electronic media. In this electronic contract agreement is an agreement of the parties that is carried out through an electronic system. From the background above, the formulation of the research problem is How the Legitimacy of Electronic Contract Agreements in E-Commerce Transactions Viewed from Civil Law. This study uses a normative research method, namely studying problems by processing data obtained from laws and regulations in accordance with existing rules and norms or norms as a basis for research. Articles 5 and 6 of the ITE Law state that electronic information, documents and signatures can be used as evidence in e-commerce transactions that are considered valid as long as the information can be checked, downloaded, displayed, guaranteed and accountable. This article is emphasized by the explanation of article 5 of Law Number 19 of 2016. Keywords: Legitimacy, Agreement, E-Commerce